Radiotherapy for brainstem gliomas in children and adults: A single‐institution experience and literature review. Issue 2 (3rd March 2016) - Yoshida, Kenji; Sulaiman, Nor Shazrina; Miyawaki, Daisuke; Ejima, Yasuo; Nishimura, Hideki; Ishihara, Takeaki; Matsuo, Yoshiro; Nishikawa, Ryo; Sasayama, Takashi; Hayakawa, Akira; Kohmura, Eiji; Sasaki, Ryohei
Abstract: Aim: To evaluate the treatment results of radiotherapy (RT) in children and adults with brainstem gliomas (BSGs) and review the previous literature. Methods: Thirty patients (14 children, 16 adults) with BSG treated using RT were retrospectively evaluated. The median ages of the children and adults were 8 years (range: 2–16 years) and 49 years (range: 19–75 years), respectively. A histological diagnosis was obtained in 11 patients. The median total radiation dose was 56 Gy (range: 50–70 Gy) with a single fraction size of 1.8–2.0 Gy. Temozolomide was administered concurrently with RT in 14 patients. Results: Tumor progression after RT occurred in 26 patients (14 children and 12 adults). Four adults survived without tumor progression. The median survival times for children and adults were 8.5 and 39 months, respectively. The 1‐, 2‐ and 3‐year overall survival rates for children/adults were 29%/75%, 14%/68% and 0%/53%, respectively ( P = 0.001), and the 1‐, 2‐ and 3‐year progression‐free survival rates for children/adults were 14%/69%, 0%/49% and 0%/35%, respectively ( P < 0.001). Grade 3 or higher acute and late toxicities did not occur. Conclusion: In this study, the prognosis of children with BSGs was considerably poorer than that of adults, and our results are consistent with those of previous studies. Efforts should be made to improve the survival outcomes of patients with BSGs, especially children.